Muhammad Faizar's Da'wah Strategy to Increase Religious Awareness Through Youtube - Ismail, Ismail; Aditya, Ari Dwi; Aunillah, Nur (Palakka : Media and Islamic Communication, 2024)
This study aims to find out the da'wah strategy used by Muhammad Faizar on the social media platform YouTube. This research has a focus on increasing Muslim awareness of Islamic teachings. The technique used is a framing analysis technique in collecting data from videos uploaded by Muhammad Faizar to identify and evaluate important elements in forming his da'wah strategy. Content in the form of videos is thoroughly analyzed by considering the type of content, the use of language, interactive approaches, and the use of social media. This da'wah strategy brings the dai and mad'u closer to each other allowing the exchange of ideas and ideas, giving the mad'u the opportunity to ask questions and give feedback. The results of this research provide valuable knowledge about effective da'wah methods and strategies in today's digital era.